Faunal diversity of hill ecosystems with special reference to reptiles (Zoological Records and Reviews, 2023)
Hill ecosystems of the Eastern Ghats represent a biologically significant but comparatively understudied zone withinpeninsular India, harbouring a transitional fauna at the confluence of Deccan Plateau, Eastern Ghats scrub forest, andlowland Andhra coastal influences. Reptiles are particularly well-represented in these dry and rocky hill habitats, wherethe thermal heterogeneity of boulder fields, rocky escarpments, and scrub woodland provides diverse microhabitats forectothermic vertebrates. This study presents a comprehensive faunal diversity assessment of Eastern Ghats hillecosystems in Andhra Pradesh and Telangana, with special reference to reptile diversity, based on systematic surveys at44 sites across five hill ranges during wet and dry seasons over two years (2020-2022). A total of 284 faunal species aredocumented, including 124 reptile species from 28 families. Twelve new district records and 4 candidate new species aredocumented among the reptiles. Rocky outcrops, elevation range, and distance from nearest settled area are thestrongest predictors of reptile species richness. Fourteen reptile species are IUCN Threatened. Updated identificationkeys and distribution maps for the 124 documented reptile species are provided.